2017
DOI: 10.1016/j.chb.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of user engagement in online brand communities: Evidence from Twitter

Abstract: Social media such as forums, blogs and microblogs has been increasingly used for public information sharing and opinions exchange nowadays. It has changed the way how online community interacts and somehow has led to a new trend of engagement for online retailers especially on microblogging websites such as Twitter. In this study, we investigated the impact of online retailers' engagement with the online brand communities on users' perception of brand image and service. Firstly, we analysed the overall sentime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 70 publications
4
96
0
2
Order By: Relevance
“…Furthermore, online communities are used by brands to collect relevant insights and knowledge relating to their business activities (Adjei, Noble, & Noble, ). Thus interactivity through communities from shared information can lead to attitude change, cognitive involvement in the SM experience, and influence SM users’ feelings (Ibrahim et al, ; Smith & Gallicano, ). SM experts also suggest that interactivity through convincing storytelling is an effective approach to influencing users’ attitudes and intentions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, online communities are used by brands to collect relevant insights and knowledge relating to their business activities (Adjei, Noble, & Noble, ). Thus interactivity through communities from shared information can lead to attitude change, cognitive involvement in the SM experience, and influence SM users’ feelings (Ibrahim et al, ; Smith & Gallicano, ). SM experts also suggest that interactivity through convincing storytelling is an effective approach to influencing users’ attitudes and intentions.…”
Section: Discussionmentioning
confidence: 99%
“…From a marketing communications perspective, social media (SM) provides a vehicle for companies to share information relating to their brands, and a forum for consumers to interact with other users in their network (Kumar, Choi, & Greene, ; Rapp, Beitelspacher, Grewal, & Hughes, ). SM has become a key area of research on brands as it offers the opportunity to use interactive platforms for the creation and exchange of information, and exploits its marketing potential (Ibrahim, Wang, & Bourne, ). In recent years, the popularity of SM for connecting and cooperating with customers has increased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…In the SM context, research on the consumer's exposure to SM brand-related communication was shown to positively impact perceptions of brands (Bruhn et al, 2012;Schivinski & Dabrowski, 2015. Although SM brand-related communication appears to influence consumers' attitudes, its investigation is still warranted given that the literature on SM brand-related communication is scattered (Moro, Rita, & Vala, 2016), and varies across industries and sources (Bruhn et al, 2012;Schivinski & Dabrowski, 2015, contexts (Ibrahim, Wang, & Bourne, 2017), and business orientations (Huotari, Ulkuniemi, Saraniemi, & Mäläskä, 2015). To advance research on the effects of SM brandrelated communication on consumers' attitudes and a priori in which consumers exposed to this type of communication are positively influenced in their intentions to participate in brand-sponsored events.…”
Section: Social Media Brand-related Communicationmentioning
confidence: 99%
“…According to [27], Text Mining (TM) can be defined as an analytic process that is designed to explore the unstructured text documents in search of useful information and knowledge hidden from a large amount of text resources. TM has been widely applied in many application domains such as military knowledge [28][29][30][31], business analytics [32][33][34], documents analysis [35][36][37], social media issues [38][39][40], etc. In this research, TM which is one of DM method is explored as to find new knowledge through examining qualitative data of patient experiences while having chemo treatment [20,21].…”
Section: Background and Related Workmentioning
confidence: 99%